Short Communication: A 24 Hour Ecotoxicity Test for Acid Mine Drainage Using Hatching Success in Daphnia magna - E Aluma; K Johnson (Journal of Applied Sciences and Environmental Management, 2011)
A bioassay utilizing the cladoceran Daphnia magna hatching success is presented for testing the toxicity of acid mine drainage (AMD) sediments. AMD sediments contain complex mixtures of potential toxins and a rapid, sensitive bioassay is valuable for assessing toxicity in the field, particularly after transient environmental events. Daphnia magna was incubated in water exposed to 1. clean sand spiked with different proportions of a mixture of metal salts and 2. sand mixed with different proportions of AMD sediments. Hatching success was linearly related to both the proportion of artificially spiked sediments (r= -0.83; p= 0.0002) and the proportion of AMD sediments (r = - 0.74; p= 0.02) that Daphnia magna was exposed to during incubations. No animals hatched during the first 18 hrs of observation under any treatments, so a single observation at 24 h is practical for this assay. The assay should be generally applicable to toxicity testing, particularly when assessing complex mixtures of pollutants in field settings. The novelty of the proposed study lies in the fact that it proposes the fastest ecotoxicity assay that we know of using Dahpnia magna. Potentially, after appropriate calibration for the particular pollutant of interest, it could be used to test for a wide array of aquatic pollutants. @JASEM